2000
DOI: 10.1590/s0103-50532000000400007
|View full text |Cite
|
Sign up to set email alerts
|

Direct analysis of Antarctic krill by slurry sampling: determination of copper, iron, manganese and zinc by flame atomic absorption spectrometry

Abstract: A técnica de amostragem de suspensão aliada à espectrometria de absorção atômica com chama foi empregada para a determinação direta de Cu, Fe, Mn e Zn em matrizes de Krill antártico. O efeito dos parâmetros instrumentais e o preparo das suspensões foram estudados em função do sinal analítico. Para a determinação de Cu, Fe e Zn, as amostras foram suspensas em uma solução de HNO 3 2,0 mol L -1 e para a determinação de Mn, o krill foi suspenso em uma solução de HNO 3 4,0 mol L -1 . A precisão entre as replicas fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
0
12
0
5
Order By: Relevance
“…As nitric acid is generally used for sample extraction/decomposition [17][18][19] and because it provides a good medium for working with FAAS technique, [20][21][22] it was chosen as the extracting medium for this purpose.…”
Section: Ultrasound-assisted Extraction: Effects Of Acid Concentratiomentioning
confidence: 99%
See 1 more Smart Citation
“…As nitric acid is generally used for sample extraction/decomposition [17][18][19] and because it provides a good medium for working with FAAS technique, [20][21][22] it was chosen as the extracting medium for this purpose.…”
Section: Ultrasound-assisted Extraction: Effects Of Acid Concentratiomentioning
confidence: 99%
“…17 Embryogenic and non-embryogenic Citrus samples of 150 mg were weighted and transferred to a Teflon vessel, in which 6 mL of HNO 3 (concentrated ) + 1 mL of H 2 O 2 (30% v v -1 ) were added. The solution was heated by microwave action only after the initial reaction had subsisted.…”
Section: Accuracy Check For Ultrasound Extractionmentioning
confidence: 99%
“…Para as amostras de lapa, não foi realizado um estudo com relação ao tamanho de partícula. Optou-se em utilizar diretamente um diâmetro de 63 µm, em virtude de estudos realizados previamente 18 . Utilizando este tamanho de partícula as recuperações para Cu e Zn foram de 94,9 e 101%, respectivamente.…”
Section: Resultados E Discussão Estabilidade Da Suspensãounclassified
“…Recent applications for samples of river sediments (Alves et al 2001a,b) and Antarctic krill (Alves et al 2000) have demonstrated that slurries can also be successfully analysed by flame atomic absorption spectrometry.…”
Section: Recent Advances For Metal Determinationsmentioning
confidence: 99%